Teologi Inklusif Kehidupan Pesantren: Tasamuh Sebagai Etika Sosial - Akmal Rizki Gunawan; Syamsul Wathani; Yoyo Hanbali; Muhammad Roni (Program Pascasarjana, Universitas Islam Bunga Bangsa Cirebon, 2021)
“The presence of Islamic boarding schools in Indonesia is a display case for the distinctive face of Islam, with social, cultural, religious and political arrangements for civil society. Pesantren becomes an educational institution as well as a house of wisdom, where students and the pesantren community learn to be good individuals. The strengths of the educational, ethical and socio-religious principles of Islamic boarding schools need to be discussed more deeply, in order to explore the richness of inclusiveness in Islamic boarding schools. Inclusiveness is a result of pesantren cultural education, and inclusiveness is the result of pesantren curriculum education. The principle of inclusiveness in Islamic boarding schools can be seen in the realm of social interaction, not in the realm of ideas. Education carried out in Islamic boarding schools is education that is integrated in three intelligences at once; intellectual, spiritual and emotional. The educational culture of this pesantren is unique. Where the value of education forms the value in a santri from the formation of classical book studies with a Sufism or Sufism pattern. Education in Islamic boarding schools prioritizes the theological-philosophical goals of Islamic education. In addition to seeking knowledge (li talab al-ilm) also seeking blessings (li talab al-barakah). Tasamuh, gentle, calm attitude, respect, respect for others, open thinking (inclusive), are authentic social ethics of Islamic boarding school products. Tasamuh, Islamic boarding schools are not only theoretical, but become a way of life (al-'amal al-hayah). The social ethics of Islamic education in Islamic boarding schools lies in the ability to optimize -spiritual- tarbiyah, ta'lim -intellectual-, ta'dib -emotional- education which is the spirit of Islamic education. Pesantren has an exclusive and inclusive attitude that is well harmonized.”. ABSTRAK “Kehadiran pondok pesantren di Indonesi menjadi etalase wajah beragama Islam yang khas, dengan tatatan sosial, budaya, agama dan politik masyarakat madani. Pesantren mejadi lembaga pendidikan sekaligus rumah kearifan, dimana santri dan masyarakat pesantren belajar menjadi pribadi yang baik. Kekuatan prinsip pendidikan, etika dan sosial-religius pesantren perlu diwacanan lebih dalam, guna menggali kekayan khazanah inklusifitas di pondok pesantren. Inklusifitas merupakan sebuah hasil dari pendidikan kultur pesantren, dan sikap inklusif merupakan hasil dari pendidikan kurikulum pesantren. Prinsip inklusif di pondok pesantren dapat dilihat dalam ranah interaksi sosial, bukan pada dataran ide. Pendidikan yang dilaksanakan di pesantren adalah pendidikan yang digabungkan (integrated) dalam tiga kecerdasan sekaligus; intelektual, spiritual dan emosional. Kultural edukatif pesantren ini menjadi khas. Dimana nilai kendidikan membentuk nilai dalam diri seorang santri dari bentukan kajian kitab klasik yang bercorakan tasawwuf atau sufistik. Pendidikan di pondok pesantren mengendepankan tujuan teologis-filosofis pendidikan Islam. Selain mencari ilmu (li thalab al-ilm) juga mencari keberkahan (li thalab al-barakah). Tasamuh, sikap lembut, teduh, menghargai, menghormai orang lain, berfikir tebuka (inklusif), merupakan etika sosial otentik produk pondok pesantren. Tasamuh, pondok pesantren tidak hanya teoritis, melainkan menjadi sebuah laku hidup (al-‘amal al-hayah). Etika sosial pendidikan Islam pondok pesantren terletak pada kemampuan dalam mengoptimalkan Pendidikan tarbiyah ¬-spritual- , ta’lim -intelektual-, ta’dib -emosional- yang menjadi ruh pendidikan Islam. Pesantren memiliki sikap eksklusif serta inklusif yang diharmonisasikan dengan baik.”.